Case-control study of self reported genitourinary infections and risk of gastroschisis: findings from the national birth defects prevention study, 1997-2003. Issue 7658 (16th June 2008) - Feldkamp, Marcia L; Reefhuis, Jennita; Kucik, James; Krikov, Sergey; Wilson, Andy; Moore, Cynthia A; Carey, John C; Botto, Lorenzo D
Abstract : Objective To assess the association between genitourinary infections in the month before conception to the end of the first trimesterand gastroschisis. Design Case-control study with self reported infections from a computer assisted telephone interview. Setting National birth defects prevention study, a multisite, population based study including 10 surveillance systems for birth defects in the United States. Participants Mothers of 505 offspring with gastroschisis and 4924 healthy liveborn infants as controls. Main outcome measure Adjusted odds ratios for gastroschisis with 95% confidence intervals. Results About 16% (n=81) of case mothers and 9% (n=425) of control mothers reported a genitourinary infection in the relevant time period; 4% (n=21) and 2% (n=98) reported a sexually transmitted infection and 13% (n=67) and 7% (n=338) reported a urinary tract infection, respectively. Case mothers aged <25 years reported higher rates of urinary tract infection alone and in combination with a sexually transmitted infection compared with control mothers. In women who reported both types of infection, there was a greater risk of gastroschisis in offspring (adjusted odds ratio 4.0, 95% confidence interval 1.4 to 11.6). Conclusion There is a significant association between self reported urinary tract infection plus sexually transmitted infection just before conception and in early pregnancy and gastroschisis.